Gamification As a Determinant of Effective and Efficient Skills Improvement - Miroslaw BETKOWSKI (Communications of International Proceedings, 2022)
In today's easy access to unlimited amounts of information, human ability to obtain effective knowledge is not a problem. The acquisition of knowledge and its optimal use becomes a feature that plays a decisive role in the manager's management. One of the tools that allows the effective use of knowledge resources is gamification. Gamification is a tool with specific mechanisms and techniques of effectiveness as well as a concept that shapes people's behavior. This tool is used in business, human resource management and nowadays more and more often in education. This article is the result of research on gamification as a method of academic education. Solutions using gamification schemes that were directly applied during classes on a representative group of students were presented. The author will present the results of the survey among the respondents in the second part of the article The article is an attempt to show gamification as a tool to mark the value of the education process and as a form of diversification and supplementation of academic education programs.
Keywords: Gamification; gamification processes; gamification programs; knowledge; science; management